Characterisation of meteotsunami signatures in tide gauge records: a case study on the 2022 Hunga Tonga-Hunga Ha’apai eruption - Gong, Deyang (Nanyang Technological University, 2025)
Meteotsunamis are long-wavelength, oceanic waves triggered by atmospheric pressure disturbances. Understanding meteotsunamis is crucial since they can potentially damage coastal infrastructure and endanger public safety as demonstrated at Dayyer, Persian Gulf in Iran on 19 March 2017, which killed 5 people and left 22 injured. Despite its importance, the characteristics of meteotsunami are not very well explored due to the scarcity of events and short instrumentation duration. Hence, part of this research project aims to address the research gap by investigating the occurrence of meteotsunami from the 15 January 2022 eruption of Hunga Tonga–Hunga Haʻapai, a submarine volcano in the Kingdom of Tonga, through analysing tide gauge records. We will analyse tide gauge data, which measures the variation in sea level over time at a specific location near east Australia. Fast Fourier Transform (FFT) is applied to the tide gauge data before and after the eruption respectively with different time durations with a focus on the 1-day and 3-day period to identify patterns that could be characteristic of meteotsunami. After which, this research will extend its FFT analysis to filter additional tide gauges in prominent port cities like Singapore and Hong Kong which have no historical record of a meteotsunami. Ultimately, the research findings could be used to assist in the improvement of coastal safety and disaster preparedness such as the development of effective early warning systems, thus enhancing the Southeast Asia and East Asia regions' abilities to anticipate and mitigate the impacts of meteotsunamis along coastal areas.